2019
DOI: 10.1111/gbb.12569
|View full text |Cite
|
Sign up to set email alerts
|

Twin‐based heritability of actimetry traits

Abstract: There is a critical need for phenotypes with substantial heritability that can be used as endophenotypes in behavioral genetic studies. Activity monitoring, called actimetry, has potential as a means of assessing sleep and circadian rhythm traits that could serve as endophenotypes relevant to a range of psychopathologies. This study examined a range of actimetry traits for heritability using a classic twin design. The sample consisted of 195 subjects from 45 monozygotic (MZ) and 50 dizygotic (DZ) twin pairs ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…An individual’s phase of entrainment under a specific zeitgeber signal could well be thought of as a stable trait. However, since the zeitgeber signal people are exposed to can greatly vary in strength and timing, chronotype in the real world may rather represent a state than a trait—making genetic studies based on real-world data particularly difficult but highlighting the breadth of possible states of the circadian system [57].…”
Section: Chronotypementioning
confidence: 99%
“…An individual’s phase of entrainment under a specific zeitgeber signal could well be thought of as a stable trait. However, since the zeitgeber signal people are exposed to can greatly vary in strength and timing, chronotype in the real world may rather represent a state than a trait—making genetic studies based on real-world data particularly difficult but highlighting the breadth of possible states of the circadian system [57].…”
Section: Chronotypementioning
confidence: 99%
“…López-Mínguez et al (2017), using a composite measure (considering wrist temperature, activity and position), found a heritability of 65% and 61% for duration of night-time and diurnal sleep respectively. More recently, another study using actigraphy reported 49% heritability for total sleep and 44% for the mean duration of sleep episodes (Gehrman et al, 2019).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…An individual's phase of entrainment under a specific zeitgeber signal could well be imagined as a stable trait. However, since the zeitgeber signal people are exposed to can greatly vary in strength and timing, chronotype in the real world may rather represent a state than a trait -making genetic studies based on real-world data particularly difficult but highlighting the breadth of possible states of the circadian system [51].…”
Section: The Stability Of Chronotype -State or Trait?mentioning
confidence: 99%